Changes on aortic diameter and number of Endothelin-B receptor in aortic endothelium of diabetes mellitus rat model after exercise - Pramaningtyas, Miranti Dewi; Utoro, Totok; Purwono, Setyo; Agustiningsih, Denny (Bangladesh Journal of Medical Science, 2016)
Background: Incidence and prevalence rate of diabetes mellitus (DM) were increased in recent years in various parts of the world. Diabetes mellitus had microvascular and macrovascular complications. Those complications of DM occurred due to vascular disorders. The complications include the decrease of endothelin B receptor (ETB) and reduce on blood vessels diameter. In vitro studies indicate shear stress can increase expression of ETB receptors on the endothelium. ETB receptors in endothelium have vasodilatation activity. Shear stress increases in physical exercise. Physical exercise known may improve ETB receptor number and also increase the diameter of blood vessels. Objective: This study aims to know the changes of aortic diameter and the number of ETB receptor expression in the aortic endothelium of DM rat model after exercise. Methods: This study is an experimental research design with a post-test only control group to measure the diameter of the aorta and ETB receptor expression in the aortic endothelium. Rat model of DM obtained by injecting streptozotocin 35mg/kgwb intra peritoneal Sprague Dawley male rats aged 11-12 weeks. Rats were divided into two groups, one group received regular physical exercise and other group without regular physical exercise. Physical exercise routine using a special treadmill for rat, low - moderate intensity, frequency 5x/week, for 9 weeks, with a week of adaptation using a speed of 5 m/min for 10 minutes, followed 8 weeks later using a gradual rise velocity of 5 m/min to 20 m/min for 60 minutes. Rat aortic diameter was measured by using a microscope optilab. Endothelin B receptor expression was calculated by the percentage of the ETB receptor in aortic endothelium which has been stained with immunohistochemical staining. Results: The mean results for the aortic lumen diameter in non-exercise group rat is 913.73 ± 62.08 ?m, and 1066.73 ± 28.58 ?m in exercise group (p value is 0.033). After immunohistochemistry staining for ETB, the results for non-exercise group is 49.37 ± 5.64 %, while for the exercise group the ETB receptors is 78.42 ± 5.84 % (p value is 0.006). Conclusion: There was an increasing of ETB receptor number and aortic diameter of DM rat model after regular physical exercise compared with the group of DM rat model without regular physical exercise. Bangladesh Journal of Medical Science Vol.15(3) 2016 p.381-384